2019
DOI: 10.18773/austprescr.2019.070
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive drugs and driving

Abstract: Any drug or substance with effects on the central nervous system can impair the ability to drive safely.When prescribing, consider the effects of each drug on driving as well as the use of other substances. Advise the patient of the risks.Opioids, benzodiazepines, anticonvulsants, antipsychotics and sedating antidepressants increase the risk of crashing. Erratic use of sedatives causes a higher level of impairment than stable regimens.Patients who have complex medical conditions and take multiple drugs should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Besides, the anti-COVID-19 restrictive measures modified the drug offer and altered substance misuse patterns. Drug-related phenomena like the drugs-and driving and drug parties are expected to decrease (17,18). Due to high addiction liability, we suppose that the global shortage of heroin may have forced regular users to take other substances with similar effects, such as fentanyl analogs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the anti-COVID-19 restrictive measures modified the drug offer and altered substance misuse patterns. Drug-related phenomena like the drugs-and driving and drug parties are expected to decrease (17,18). Due to high addiction liability, we suppose that the global shortage of heroin may have forced regular users to take other substances with similar effects, such as fentanyl analogs.…”
Section: Discussionmentioning
confidence: 99%
“…These are often used in combination with alcohol by people of all ages. 17 Polypharmacy (taking five or more unique medicines daily) is an alert for possible driving impairment risk. 15 An analysis of Australian Pharmaceutical Benefits Scheme dispensing data found that between 2006 and 2017 the prevalence of taking five or more medicines increased from 33 to 36% in Australians aged 70 years and over.…”
Section: Medicines and Drivingmentioning
confidence: 99%
“…[19][20][21] Other ways that medicines may adversely affect driving are effects on balance, vision, judgement, aggression, risk-taking, psychomotor coordination, vigilance and attention. 10,17,[19][20][21] The issue is further complicated by road users omitting to take prescribed medication, doubling up (e.g. due to confusion with generic medicines), taking medicines at inappropriate times, taking alcohol with medicines, or taking additional non-prescription medicines or complementary medicines and then driving, oblivious to potential dangers.…”
Section: Impact Of Medicines On Drivingmentioning
confidence: 99%
See 2 more Smart Citations